I have the question factor this problem, 2x^2+5x-3. And I was told to multiply 2 by -3, which the answer is -6. And then add the factors of -6 to get the middle number. Which -1 plus 6 is 5 for 5x. But when I put (x-1)(x+6) I don't get 2x^2+5x-3. What
am I doing wrong?

## How to factor 2x^2+5x-3?

Tutors, please sign in to answer this question.

# 1 Answer

2 X

^{2}+ 5X - 3 =0 have to chose 2 numbers whose product is -3( 2) = -6 and sum = 5 = 6 -1

+6 , -1

Break 5X to 6X - X

2X

^{2}+ 6X - x - 3 =0 2X( X + 3 ) - ( X + 3) = 0 Factor by grouping

( X + 3 ) ( 2X -1 ) = 0

X +3 = 0 X =-3 2X -1 = 0
X = 1/2